2018
DOI: 10.12693/aphyspola.133.843
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Luminescence Properties of Pr3+-Doped BiPO4 Polycrystals

Abstract: The results of synthesis, crystal structure characterization and luminescence properties study of the Pr 3+-doped bismuth orthophosphate, BiPO4, polycrystals are reported. It was found that doping of bismuth orthophosphate with praseodymium of concentration more than 1% leads to phase transition of BiPO4 from so-called "hightemperature monoclinic" to "low-temperature monoclinic" structure. At room temperature studied samples revealed intensive red luminescence caused by radiation electronic transitions in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Several studies have observed that the emission of the 1 D 2 → 3 H 4 transition of Pr 3+ disappears upon increasing the Pr 3+ concentration . In this case, the Pr 3+ concentration was kept at 1% in all samples.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have observed that the emission of the 1 D 2 → 3 H 4 transition of Pr 3+ disappears upon increasing the Pr 3+ concentration . In this case, the Pr 3+ concentration was kept at 1% in all samples.…”
Section: Resultsmentioning
confidence: 97%
“…However, a reduced intensity of the peaks observed at around 600 nm can be clearly recognized (inset). These peaks have been attributed to the 1 D 2 → 3 H 4 and 3 P 0 → 3 H 6 transitions of the Pr 3+ ion …”
Section: Resultsmentioning
confidence: 99%